2022
DOI: 10.3389/fmicb.2022.977292
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota modulation by plant polyphenols in koi carp (Cyprinus carpio L.)

Abstract: Plant polyphenol supplementation may improve fish health in aquaculture systems. To assess the potential benefits and function mechanism of plant polyphenols in aquaculture, fish were fed either basal feed (CON) or the basal feed supplemented with 500 mg/kg of curcumin (CUR), oligomeric proanthocyanidins (OPC), chlorogenic acid (CGA), or resveratrol (RES). After an 8-week feeding experiment, blood samples were used to analyze the concentrations of biochemical indices. Gut samples were collected to evaluate mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Therefore, we speculated that carnivorous rainbow trout need more microbial assistance in digesting plant-based protein and fat. Moreover, the modules with Enterococcus [ 45 ], Clostridium [ 36 , 37 ], Exiguobacterium [ 46 , 47 ], Sphingomonas [ 48 ], and Bacteroides [ 49 ] as hub nodes might be beneficial for the utilization of the plant diets and the maintenance of fish intestinal microfloral stability in the FMR group, as some studies have confirmed that species from these bacterial genera are beneficial to fish. For example, the Enterococcus genus could enhance fish growth, modulate the gut microbiota to suppress inflammatory responses, and boost the immune system [ 45 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculated that carnivorous rainbow trout need more microbial assistance in digesting plant-based protein and fat. Moreover, the modules with Enterococcus [ 45 ], Clostridium [ 36 , 37 ], Exiguobacterium [ 46 , 47 ], Sphingomonas [ 48 ], and Bacteroides [ 49 ] as hub nodes might be beneficial for the utilization of the plant diets and the maintenance of fish intestinal microfloral stability in the FMR group, as some studies have confirmed that species from these bacterial genera are beneficial to fish. For example, the Enterococcus genus could enhance fish growth, modulate the gut microbiota to suppress inflammatory responses, and boost the immune system [ 45 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…With 300 mg/kg OPC supplemented in the diet, the lower values of parameters related to alpha diversity of intestinal microbiota were increased in present research. The improvement of the abundance and diversity of the intestinal microbiota was also found in hybrid sturgeon [12], juvenile American eel [22], and carp [53] fed diets with OPC supplementation under no designed stress condition.…”
Section: Effects Of Opc On the Intestinal Microbiota Of Juvenile Amer...mentioning
confidence: 92%
“…Dietary 50 mg/kg OPC supplementation could decrease the relative abundance of Aeromonas in the intestine of hybrid sturgeon [12]. OPC might act as the substrate to stimulate probiotic colonization in the intestine of carp [53]. In a vitro experiment, OPC was found to alleviate the amount of Escherichia coli and Salmonella typhimurium adhered to IPEC-J2 cells [59].…”
Section: Effects Of Opc On the Intestinal Microbiota Of Juvenile Amer...mentioning
confidence: 97%
“…In contrast, studies conducted in pigs (Choy et al 2014;Fiesel et al 2014) demonstrated that the administration of grape seed extract induced an ecological shift in the microbiome, reducing the amount of certain bacterial groups (such as Streptococcus and Clostridium) while increasing others (such as Lachnospiraceae, Lactobacillus, and Ruminococcus). In the case of fish, a study by Zhang et al (2022) revealed that supplementing the diet of koi carp (Cyprinus carpio) with resveratrol increased gut bacterial richness, whereas no significant effect was observed with other polyphenols like curcumin or chlorogenic acid.…”
Section: Changes In Fillet Quality During Storagementioning
confidence: 99%